A red-emission fluorescent probe for visual monitoring of lysosomal pH changes during mitophagy and cell apoptosis. Issue 21 (1st September 2020) - Wang, Xiaodong; Fan, Li; Zhang, Xiaoran; Zan, Qi; Dong, Wenjuan; Shuang, Shaomin; Dong, Chuan
Abstract : We report a red-emission pH fluorescent probe (MSO) for visual monitoring of lysosomal pH changes during mitophagy and cell apoptosis in living cells. Abstract : We presented a novel red-emission fluorescent probe (MSO ) for selectively monitoring lysosomal pH fluctuation in living cells. The probe was designed by employing rhodamine B as the off-on pH sensitive moiety owing to the unique spirocycle group and morpholine as the lysosome targetable unit. Based on the H + -induced spirocyclic ring opening process, MSO displayed significant pH sensing properties around 590 nm, with a p K a value of 5.42 and a good linear pH response ranging from 5.00 to 6.00. Besides, the probe possessed other prominent photophysical properties such as good selectivity and excellent photostability as well as low cytotoxicity, together making the red-emission probe more favorable for long-time and real-time imaging in live cells. Furthermore, MSO selectively accumulated into lysosomes and successfully visualized the mitophagy, cell apoptosis and heat shock processes by monitoring the rise of lysosomal pH.